Carbon materials for ion-intercalation involved rechargeable battery technologies - Wang, Gang; Yu, Minghao; Feng, Xinliang (Chemical Society reviews, 2021)
The ever-increasing energy demand motivates the pursuit of inexpensive, safe, scalable, and high-performance rechargeable batteries. Carbon materials have been intensively investigated as electrode materials for various batteries on account of their resource abundance, low cost, nontoxicity, and diverse electrochemistry. Taking use of the reversible donor-type cation intercalation/de-intercalation (including Li , Na , and K ) at low redox potentials, carbon materials can serve as ideal anodes for 'Rocking-Chair' alkali metal-ion batteries. Meanwhile, acceptor-type intercalation of anions into graphitic carbon materials has also been revealed to be a facile, reversible process at high redox potentials. Based on anion-intercalation graphitic carbon materials, a number of dual-ion battery and Al-ion battery technologies are experiencing booming development. In this review, we summarize the significant advances of carbon materials in terms of the porous structure, chemical composition, and interlayer spacing control. Fundamental mechanisms of carbon materials as the cation host and anion host are further revisited by elaborating the electrochemistry, intercalant effect, and intercalation form. Subsequently, the recent progress in the development of novel carbon nanostructures and carbon-derived energy storage devices is presented with particular emphasis on correlating the structures with electrochemical properties as well as assessing the device configuration, electrochemical reaction, and performance metric. Finally, perspectives on the remaining challenges are provided, which will accelerate the development of new carbon material concepts and carbon-derived battery technologies towards commercial implementation.